Gaze doesn't always lead steering. (December 2018) - Lehtonen, Esko; Lappi, Otto; Koskiahde, Noora; Mansikka, Tuomas; Hietamäki, Jarkko; Summala, Heikki
Highlights: The coordination of gaze and steering was studied in an on-road study. Drivers often returned their gaze back to the road ahead before making steering corrections. The eccentricity of the off-road target influences gaze-steering coordination. Abstract: In car driving, gaze typically leads the steering when negotiating curves. The aim of the current study was to investigate whether drivers also use this gaze-leads-steering strategy when time-sharing between driving and a visual secondary task. Fourteen participants drove an instrumented car along a motorway while performing a secondary task: looking at a specified visual target as long and as much as they felt it was safe to do so. They made six trips, and in each trip the target was at a different location relative to the road ahead. They were free to glance back at the road at any time. Gaze behaviour was measured with an eye tracker, and steering corrections were recorded from the vehicle's CAN bus. Both in-car ' Fixation ' targets and outside ' Pursuit ' targets were used. Drivers often used a gaze-leads-steering strategy, glancing at the road ahead 200–600 ms before executing steering corrections. However, when the targets were less eccentric (requiring a smaller change in glance direction relative to the road ahead), the reverse strategy, in which glances to the road ahead followed steering corrections with 0–400 ms latency, was clearly present. The observed use of strategies can be interpreted in terms of predictive processing: The gaze-leads-steering strategy is driven by the need to update the visual information and is therefore modulated by the quality/quantity of peripheral information. Implications for steering models are discussed.